Pressure as effective green technology for synthesis of polyfunctionally substituted heteroaromatics: Synthesis of a variety of pyrazolo[1,5-a]pyrimidines - AlMarzouq, Douaa Salman; Zaky, Omniya Sayed; AlNajjar, Abdulaziz Abdulrazaq; Sadek, Kamal Usef (European Journal of Chemistry, 2016)
Pyrazole molecules are in the forefront of organic chemistry due to their various encompass substituents, which have many biological activity sequence. The biological and medicinal activities of pyrazolo[1,5-a]pyrimidines have received considerable interest in this regard. We reported here a comparison between reaction of 4-phenylazo-3,5-diaminopyrazole (4) with ethyl propiolate (15), dimethylacetylene dicarboxylate (20), diethyl fumarate (25) and benzylidenemalononitrile (11) in the presence of catalytic amount of piperidine. We initially followed literature procedure (method A), then utilizing ultrasound irradiation (method B), microwave heating (method C) and in a Q-tube (method D). We confirmed the structure of the product by analytical spectroscopic methods. Method (D) gave a good yield with a record reaction time.